Perceived reciprocal value of health professionals' participation in global child health-related work - Sarah Carbone; Jannah Wigle; Nadia Akseer; Raluca Barac; Melanie Barwick; Stanley Zlotkin (BMC, 2017)
Abstract Background Leading children's hospitals in high-income settings have become heavily engaged in international child health research and educational activities. These programs aim to provide benefit to the institutions, children and families in the overseas locations where they are implemented. Few studies have measured the actual reciprocal value of this work for the home institutions and for individual staff who participate in these overseas activities. Our objective was to estimate the perceived reciprocal value of health professionals' participation in global child health-related work. Benefits were measured in the form of skills, knowledge and attitude strengthening as estimated by an adapted Global Health Competency Model. Methods A survey questionnaire was developed following a comprehensive review of literature and key competency models. It was distributed to all health professionals at the Hospital for Sick Children with prior international work experience (n = 478). Results One hundred fifty six health professionals completed the survey (34%). A score of 0 represented negligible value gained and a score of 100 indicated significant capacity improvement. The mean respondent improvement score was 57 (95% CI 53-62) suggesting improved overall competency resulting from their international experiences. Mean scores were >50% in 8 of 10 domains. Overall scores suggest that international work brought value to the hospital and over half responded that their international experience would influence their decision to stay on at the hospital. Conclusions The findings offer tangible examples of how global child health work conducted outside of one's home institution impacts staff and health systems locally.